VD_FINDINFO HC / 2011 / 370 vom 15. Juli 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 163 al. 1 CC, 163 CC, 176 al. 1 ch. 1 CC, 176 CC, 317 al. 1 CPC (CH), 317 CPC (CH)